A case of dorsal oblique fingertip amputation. Issue 1 (1st January 2017) - Takeda, Shinsuke; Tatebe, Masahiro; Morita, Akimasa; Yoneda, Hidemasa; Iwatsuki, Katsuyuki; Hirata, Hitoshi
Abstract: This study reports successful finger replantation in a patient with a dorsal oblique fingertip amputation. When repairing this unique type of injury, an evaluation of the remaining vessels is more useful for successful replantation than the anatomical zone classification. We propose that Kasai's classification is appropriate for guiding treatment.